Sequential treatment of maxillary retraction in cleft lip and palate - PU Panjun, ZHAO Huaxiang, MOU Qingnan, LIANG Rong, HOU Yuxia (Editorial Office of Stomatology, 2024)
Cleft lip and palate is a common congenital developmental defect, which is mainly manifested as congenital oral and maxillofacial malformations. In patients with cleft lip and palate, jaw deformity often involves three-dimensional orientation, among which the correction of sagittal dysmorphism is the key point and difficulty in its diagnosis and treatment. In this article, we will elaborate on the indications and corrective methods for the treatment of maxillary retraction of cleft lip and palate, and introduce our experience in the sequential treatment of cleft lip and palate maxillary retraction in order to promote the standardization of its diagnosis and treatment.